INFLUENCE OF SOLVENT TYPE ON PATCHOULI OIL EXTRACTION EFFICIENCY USING MICROWAVE-ASSISTED METHOD - Sanjaya, Andri; Mustafa, Mustafa; Sweatenia, Elisabeth Grace; Aulia, Siti Aisyah Rahimah; Rahmawati, Disty; Valiendra, Dhanda Ahmad; Damayanti, Damayanti; Fahni, Yunita; Auriyani, Wika Atro; Saputri, Desi Riana (JURNAL INTEGRASI PROSES, 2024)
Nilam (Pogostemon cablin Benth.) is an essential oil-producing plant with high economic value. Patchouli oil consists of components with a high boiling point, so it is very well used as a binding agent in the perfume industry. Patchouli oil is also used in the cosmetics and perfume industry, as well as in the food and beverage industry and the pharmaceutical industry. This study aims to determine the effect of solvent type and extraction time on the obtained patchouli oil yield and the composition of patchouli oil through gas chromatography-mass spectrometry (GC-MS) analysis. Patchouli leaves were extracted using the microwave-assisted extraction (MAE) method at 375 W microwave power with 30, 45, 60, 75, and 90-minute time variations. The solvents used in this study were hexane and ethanol with a raw material to solvent ratio of 1:15. The results showed that patchouli oil yield increased with increasing extraction time until it reached the optimum value. However, after reaching the optimum value, the yield decreased with increasing time. Patchouli oil with ethanol has the highest yield at 75 minutes of extraction time, with a yield of 28.45%, and patchouli oil with hexane has the highest yield at 45 minutes, which is 6.25%. Based on GC-MS test, patchouli oil contains patchouli alcohol, trans-caryophyllene, α-guaiene, α-patchoulene, β-patchoulene, δ-guaiene and veridiflorol. The patchouli alcohol (PA) content contained in patchouli oil with ethanol is 5.192%, while patchouli oil with hexane contains patchouli alcohol of 2.445%.